2018
DOI: 10.1016/j.str.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of ATP-Bound Human ABCF1 Demonstrates a Unique Conformation of ABC Proteins

Abstract: Gene translation requires the correct selection of start codon AUG in mRNA. ATP-binding cassette subfamily F member 1 (ABCF1) plays a key role in the accuracy of start codon selection. However, the function of human ABCF1 is not clearly understood. Here, we solve the crystal structure of an ATP-bound wild-type human ABCF1 at 2.3-Å resolution. The comparative studies indicate that the structure is in a pre-activation intermediate conformation. This conformation is stabilized by the interaction between ATP and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…ABCF1 contains two conserved nucleotide-binding domains (NBDs) and a ~ 300 amino acid N-terminal domain that is predicted to be highly disordered (Abor et al, 2018) ( Figure S5A). This is consistent with a recent structural study on ABCF1 which indicated that the Nterminal domain cannot be crystallized (Qu et al, 2018). The N-terminal domain of ABCF1 is a low-complexity region that is unusually rich in charged amino acids, of which ~40% are divided between lysine (K) and glutamic acid (E) residues (Dyson, 2016;Hansen et al, 2006;Paytubi et al, 2009) ( Figure 5A).…”
Section: Transcriptional Coactivation Mediated By the Intrinsically Dsupporting
confidence: 90%
See 1 more Smart Citation
“…ABCF1 contains two conserved nucleotide-binding domains (NBDs) and a ~ 300 amino acid N-terminal domain that is predicted to be highly disordered (Abor et al, 2018) ( Figure S5A). This is consistent with a recent structural study on ABCF1 which indicated that the Nterminal domain cannot be crystallized (Qu et al, 2018). The N-terminal domain of ABCF1 is a low-complexity region that is unusually rich in charged amino acids, of which ~40% are divided between lysine (K) and glutamic acid (E) residues (Dyson, 2016;Hansen et al, 2006;Paytubi et al, 2009) ( Figure 5A).…”
Section: Transcriptional Coactivation Mediated By the Intrinsically Dsupporting
confidence: 90%
“…First, ABCF1 is unambiguously shown to be the sole constituent of SCC-B. Second, ATP binding and hydrolysis by ABCF1 are dispensable for transcription, unlike for ABCF1's role in translation (Paytubi et al, 2009;Qu et al, 2018). Third, while the entire IDR is essential for full coactivator activity, the IDR fragment by itself is not sufficient to activate transcription.…”
Section: Transcriptional Coactivation Mediated By the Intrinsically Dmentioning
confidence: 99%
“…The two tandem ABC domains in EttA (Fig. 3A) and other ABC-F proteins share the canonical structure comprising three subdomains that is present in all ABC superfamily ATPases: (i) an F1-ATPase-like / Core subdomain with a complex topology conserved in many other ATPases including F1 and the AAA+ ATPase superfamily (as noted above); (ii) an N-terminal antiparallel -sheet (ABC ) subdomain that forms a rigid ATP-binding module together with the F1-like Core subdomain, and (iii) a 60-100 residue -helical (ABC ) subdomain containing the ABC superfamily Signature Sequence, canonically LSGGQ but generally LSGGE in proteins, inserted within the primary sequence of the F1-like Core subdomain [18,23,25,75]. The Walker A motif in the F1-like Core is a phosphate-binding loop or "P-loop" that ligates the phosphates of ATP, while Walker B motif in this subdomain is a hydrophobic -strand terminating in an aspartic acid that contributes to ligating the Mg ++ cofactor of ATP [18,25,53].…”
Section: Abc-f Protein Structurementioning
confidence: 99%
“…Structures have also been determined for two eukaryotic ABC-F proteins. The first is a crystal structure of human ABCF1 [46]. While its tandem ABC domains have essentially canonical structures, they are bound to ATP in the crystal structure, but they do not adopt the ATP-sandwich heterodimer conformation observed in all of the ribosome-bound ABC-F structures published to date, which is equivalent to the active ATP-bound conformations observed for a wide variety of ABC transporter transmembrane proteins [47][48][49].…”
Section: Accepted Articlementioning
confidence: 99%
“…The X-ray crystal structure of human ABCF1, which contains the Arm motif in ABC1, shows two protein conformations in the asymmetric unit. One of these has well-resolved electron density for the PtIM, while the Arm motif is disordered ( Figure 2B, ABCF1), and the other has weak electron density for the PtIM, while the Arm motif has well-resolved electron density [46]. These observations suggest that there is some degree of flexibility in the attachment of these structures to the ABC domains and that crystal-packing interactions possibly mimicking interactions with the ribosome control their exact orientation in the crystal lattice.…”
Section: Variable Domains Of the Familymentioning
confidence: 99%